Improving soil health and system productivity through conservation agriculture and weed management strategies in rice-maize cropping system - Sahoo, Subhra; Roy, Dhirendra Kumar; Ranjan, Shivani; Sadhu, Souvik; Sow, Sumit; Nath, Dibyajyoti; Alotaibi, Majed; Ali, Nawab; Seleiman, Mahmoud F. (Frontiers in Sustainable Food Systems, 2025)
Conservation agriculture (CA)-based rice-maize cropping system (RMCS) can be the possible option for higher productivity and maintain soil health in the Indo Gangetic Plains. However, weed infestation remains the major constraint in its adoption. Hence, to adopt CA practices and at the same time manage weed population, a field experiment was carried out at Dr. Rajendra Prasad Central Agricultural University during 2019–20 and 2020–21. Treatments consisted of four main plots of different tillage practices, viz. zero- till direct seeded rice followed by zero-till maize (ZTDSR fb ZTM), direct seeded rice followed by maize on permanent raised beds with residue (PBDSR+R fb PBDSM+R), PBDSR followed by PBDSM without residue (PBDSR-R fb PBDSM-R) and conventional tilled puddled transplanted rice followed by conventional tilled maize (CTR fb CTM). On the other hand, sub-plots comprised of five weed management options, viz. unweeded control, vermicompost mulch, P-enriched vermicompost mulch, live mulch and weed-free. The two-year study revealed that the combination of PBDSR+R fb PBDSM+R emerged as the most effective tillage practice, showing a maximum reduction in bulk density (0.07 Mg m−3) and improvements in water holding capacity by 8.1%, soil organic carbon by 8.2%, soil microbial biomass carbon by 32.7%. Among weed management practices, P-enriched vermicompost mulch resulted 18.8% higher dehydrogenase activity of soil with greater nutrient availability as compared to live mulch. In contrast, CTR fb CTM significantly deteriorated soil health. The maximum maize REY (9.3 t ha−1) and system productivity (15.9 t ha−1) were also recorded under PBDSR+R fb PBDSM+R, with increases of up to 15.2 and 25.2% over conventional practices in the second year. Overall, CA practice mainly permanent bed with residue coupled with P-enriched vermicompost mulches demonstrated strong potential for improving soil health and sustainable crop productivity in RMCS.